Of River Linkage and Issue Linkage: Transboundary Conflict and Cooperation on the River Meuse. Issue 6 (1st November 2016) - Warner, Jeroen Frank
Abstract: It is a truism in mainstream International Relations that issue linkage promotes regime formation and integration. The present article applies this idea to the transboundary lower river Meuse and finds its history of integration to be a tortuous one. Contextual political factors have at times promoted integration, at times fragmentation. The path towards regional integration, then, has not been not linear, but has consisted of conflict and cooperation, of (Meuse–Scheldt) river linkage and issue linkage, but also counterlinkage and non-linkage. Clearly linkage is not necessarily positive. I will argue that this does not need to be problematic, but suggest accepting more complexity in the analysis of river integration. I propose a way to create some order in the many available concepts of linkage to map out the role of linkage in integration.